The Effect of Running Dictation Towards Students Spelling in Writing Short Functional Text at SMP Islamic Qon - S Zakiyah, Indah; Husniah, Rohmy (Universitas Muhammadiyah Gresik, 2017)
Spelling is a key functional component of writing. In teaching learning writing, the students face some problems, which have an error in terms of spelling that influences the meaning of the word itself. Then, the teacher also has problem in teaching writing, especially spelling. The teacher requires the alternative strategy which can be used for teaching learning in writing, especially spelling. Based on previous studies, running dictation gave the positive effect such as in science of nature, listening, and speaking. Thus, making different with the previous studies, the researcher applied running dictation for teaching spelling in writing skill. This study was to investigate the significant effect of running dictation towards students spelling in writing short functional text. The design of this study was quasi experimentaldesign. The researcher chose seventh grade students of SMP Islamic Qon which totally consisted of 44 students. The researcher chose the sample of the study through population sampling. It was divided 22 students of VII-C as control group and 22 students of VII-B as experimental. The data was collected by using tests; pre-test and post-test about spelling ability in writing short functional text. After getting the data, the researcher analyzed the data using SPSS 16.00 and used Independent Sample T-test. The research finding showed that there was a significant difference between experimental group who was taught by using running dictation strategy and control group who was taught by two stay two stray. It has proven by the result of sig. (2-tailed) is .010. The sig. (2-tailed) is lower than 0.05 (0.010 < 0.05). So,null hypothesis (Ho) can be rejected. It means that running dictation strategy significantly effects on students' spelling in writing short functional text. The researcher concluded that running dictation strategy give positive effect on students’ spelling in writing ability. The students were motivated and independent in learning writing. Therefore, the researcher suggests to the English teacher for implementing of running dictation strategy as an alternative strategy in English teaching learning process. For further researchers, the researcher hopes that use of running dictation strategy in otherskills and levels to make different with the previous study.